Produção de mudas de videira cv. Bordô/Paulsen 1103 pela enxertia de mesa com estratificação - Maroli, Lari (2012)
The use of appropriate practices in the implementation of a vineyard, especially the use of grafted cuttings with good health, is an essential factor for successful viticulture in Brazil and, in particular, Southweast Paraná. The objective of this work was to test stratification temperature, type and period of grafting, for the propagation of vines, 'Bordô'/'Paulsen 1103', by bench grafting cuttings with stratification. Three experiments were developed to test these objectives. In the first and second experiment, the cuttings of the rootstock were treated with indole-butyric acid (IBA) before and after estratification, respectively. Both treatments were conducted in a randomized block in a factorial 3 x 2 (estratification temperature x grafting type), with four replications and ten units of observation (grafted cuttings). The factor estratification temperature was 19, 24, and 29 °C, while the factor grafting technique either manual top grafting or "omega" with the aid of special pliers. The third experiment was performed in randomized blocks, in a 4 x 2 factorial design, with four replications and 20 units of observation. The factor A was different period of grafting (May, June, July, and August) and the factor B was stratification temperature at two levels (19 and 24 °C). The experiments were conducted under controlled conditions (in growth chambers and in the greenhouse). The parameters evaluated at the end of stratification (21 days after grafting) were: percentage of callus formation in the region of grafting and percentage of sprouting. In the greenhouse we evaluated the development of sprouting, from day one until day 70, using a phenological scale, and measuring cuttings mortality. One hundred and twenty days after stratification we evaluated the survival of the cuttings, the development of the root system (root number and dry weight of root), shoot growth (leaf area, shoot length and dry matter). Top grafting had a higher percentage of viable grafted cuttings than the “omega” technique; temperatures of 19 and 24 °C favored the survival of the graft; while July was the most recommended period for bench grafting with stratification.